Pengaruh Orientasi Kewirausahaan, Inovasi Produk dan Teknologi Informasi terhadap Kinerja Keuangan UMKM Kuliner di Alun-alun Karanganyar - Ilham Kasanah; Edi Wibowo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was conducted on Culinary UMKM in Karanganyar Square. The purpose of this study was to analyze the significance of the influence of entrepreneurial orientation, product innovation and information technology on the financial performance of Culinary UMKM in Karanganyar Square. The type of data used in this study is quantitative. The sample of this study was 62 Culinary UMKM actors in Karanganyar Square with the type of sampling, namely accidental sampling. The analysis methods used were descriptive analysis, multiple linear regression analysis, t-test, F-test (model accuracy test), and R2 Test (determination coefficient test). The results showed that the influence of Entrepreneurial Orientation did not have a significant effect on the Financial Performance of Culinary UMKM in Karanganyar Square, thus the first hypothesis was not proven true. Product Innovation has a significant effect on the Financial Performance of Culinary UMKM in Karanganyar Square, thus the second hypothesis was proven true. Information Technology has a significant effect on the Financial Performance of Culinary MSMEs in Alun-Alun Karanganyar, thus the third hypothesis is proven true. The results of the F test obtained the results that there is an Influence of Entrepreneurial Orientation, Product Innovation and Information Technology on Financial Performance. And the results of the calculation of the determination coefficient obtained a value of R2 = 0.368, meaning that 36.8% is influenced by entrepreneurial orientation, product innovation and information technology and the rest is influenced by other variables outside the model such as financial literacy, financial inclusion, lack of capital etc.